THE DEVELOPMENT OF THE ART OF BOOKMAKING IN THE KOKAND KHANATE: SOURCES, SCHOOLS, AND CRAFTSMEN (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the formation and development of the art of bookmaking in the Kokand Khanate, its role in the socio-cultural life of the period, and its contribution to the advancement of science and education. The study highlights the creative activities of calligraphers, illuminators, painters, and manuscript decorators who worked within the khanate, while also analyzing the emergence and development of bookmaking centres. Particular attention is paid to manuscript sources, libraries, madrasas, and the court environment that influenced the growth of the art of book production. The article explores the bookmaking traditions and calligraphic schools that developed in major cultural centres such as Kokand, Margilan, Namangan, and Andijan, emphasizing their distinctive characteristics. Based on historical and scholarly sources, the research demonstrates that the art of bookmaking in the Kokand Khanate constituted an important component of the cultural heritage of Central Asia and played a significant role in the development of national written culture.
Keywords: Kokand Khanate, art of bookmaking, manuscripts, calligraphy, calligraphers, manuscript illumination, miniature painting, libraries, madrasas, scholarly heritage, manuscript sources, calligraphic schools, Fergana Valley, cultural heritage, Islamic book arts.